Influence of environment on quality hybrid seed production in castor : A case study of participatory seed production: INFLUENCE OF ENVIRONMENT ON HYBRID SEED PRODUCTION IN CASTOR : A CASE STUDY - T MANJUNATHA; C LAVANYA; K T RAMYA; J JAWAHARLAL; A VISHNUVARDHAN REDDY (Journal of Oilseeds Research, 2019)
This paper highlights the observations made regarding the influence of environmental factors on genetic purity of hybrid seed produced during the participatory seed production oftwo castor hybrids viz., DCH 177 (DPC 9 x DCS 9) and DCH-519 (M 574 x DCS 78) in two villages of Mahabubnagar district, Telangana. Preliminary observations indicated that development of environmentally sensitive interspersed staminate flowers (ISF) on pistillate lines was influenced by their genetic nature, soil and agronomic management of crop as well as weather parameters. Higher incidence of ISF was observed in shallow and red soils irrigated by furrow method compared to medium/deep, clay loamy and black soils irrigated and fertigated by drip method, leading to higher number ofselfed female plants, low genetic purity of certified hybrid seed (<85%) and rejection of seed lots during certification. Abiotic stress factors like maximum temperature (>32°C temperature) increased the number of ISF in primary spike order itself and later decreased in subsequent spike orders owing to decreased temperatures. Incidence of whiteflies and Spodoptera was particularly high in intensively cultivated agro-ecosystems. Small and marginal farmers depending on family labour were better suited for hybrid seed production of castor. Selection of suitable agro-ecosystem, farmers and their training, and genetic nature of parents proved to be critical requirements for hybrid seed production in castor.